Respuesta :

Answer:

(-2, -3)

Step-by-step explanation:

y=2x + 1

y= 0.5x - 2

2x+1= 0.5x -2

1.5x= -3

x= -2

y= 2x+ 1

y= 2(-2)+1

y= -3

The solution is (-2,-3)

The solution to the set of simultaneous equations is; (-2, -3)

We are given the equations;

y = 2x + 1   ---(eq 1)

y = 0.5x - 2   ---(eq 2)

subtract eq 2 from eq 1 to get;

0 = 2x - 0.5x + 1 - (-2)

0 = 1.5x + 3

x = -3/1.5

x = -2

Thus;

y = 2(-2) + 1

y = -4 + 1

y = -3

Read more at; https://brainly.com/question/12647791

ACCESS MORE